Unrest in the Arab World: Does Social Capital Explain Arab Springs? - Haykal, Rayan; Hariri, Nizar (European Scientific Journal, ESJ, 2017)
Using World Values Survey data (2010-2-13) on a selected number of Arab countries, this article explains that Social Capital is an important determinant of social and political stability. In the aftermath of what is commonly called Arab Spring, 3 groups of 13 countries with different levels of stability are compared using Putnamâ€™s 4 dimensions of social capital: Interpersonal Trust, Institutional Trust, Civic Engagement and Trustworthiness. On average, respondents of these countries mainly trust their family members, lack confidence in their governments, are not active members in social organizations, and rarely find illicit acts as justifiable. These four dimensions are then used in a probit regression to explain the occurrence of robberies. Our model shows that both civic norms and levels of trust have a negative and significant impact on property crimes, and that social capital could be considered as a predictor of social order. â€œTrustworthinessâ€ had the highest explanatory power, especially civic norms that proscribe stealing properties.